Putting Knowledge to Work: Outcome Performance of the UF/IFAS Welfare to Work Initiative - Elizabeth B. Bolton (EDIS)
This report, Putting Knowledge to Work: Outcome Performance of the UF/IFAS Welfare-to-Work Initiative as of May 11, 2001, is part of the UF/IFAS Welfare to Work Initiative (Grant #A6218) funded by the Florida Agency for Workforce Innovation (formerly Florida Department of Labor and Employment Security). The Principal Investigator is Elizabeth B. Bolton, Professor of Community Development, Department of Family, Youth and Community Sciences.